Therapeutic hypothermia for neonatal hypoxic ischaemic encephalopathy in Sub-Saharan Africa: A scoping review. - Naa A Buxton-Tetteh; Shakti Pillay; Gugulabatembunamahlubi T J Kali; Alan R Horn (PLoS ONE, 2025)
Introduction There are divergent views and limited data regarding therapeutic hypothermia (TH) for neonatal hypoxic ischaemic encephalopathy (HIE) in sub-Saharan Africa (SSA). Our aim was to map and synthesize the published literature describing the use of TH for HIE in SSA, and the associated outcomes. Method We searched Pubmed, Scopus, Google Scholar, and Web of Science from 1 January 1996 to 31 December 2023 for research studies, protocols, feasibility studies and surveys on term and near-term babies with HIE (population) treated with TH (concept) in SSA (context). Results Thirty records were included: Three surveys, one feasibility study and 26 publications describing 23 studies of 21 cohorts, cooling 1420 babies in South Africa, Uganda, and Ghana. There were five studies recruiting at follow-up, five pilot studies, one randomised controlled trial, one case series, and 10 birth cohorts. The methods and design of the studies were highly variable and often inadequate. Only three studies with adequately described and validated cooling methods, non-selective sequential recruitment, and neurological outcomes were identified. Two studies of babies from birth, both with intensive care facilities, reported survival with normal/mildly abnormal outcome in 71% at discharge in one study, and 71% at 12 months in another, with 16% cerebral palsy (CP) in survivors, and only 16% loss to follow-up. The third study, which only included clinic attenders after TH without intensive care, reported 7% CP in survivors, but 36% loss to follow-up. Conclusions Data from the adequately described TH studies in SSA indicate outcomes at discharge and twelve months which are similar to global norms. However, these data are limited to South Africa. Interpretation of other studies was limited by loss to follow-up, variable methodology and exclusion of babies with severe HIE in some studies. There is a need for standardised definitions to facilitate interpretation in TH studies.